Roles in ORM: A suggested semantics - Carver, Andy (Springer Berlin Heidelberg, 2011)
Evidence grows that ORM has some problems to overcome in order to escape the charge that it cannot reliably lead, as claimed, to ONF (optimal normal form) relational schemas. Some of that evidence we present here. We also indicate that there is more than one way to address the issue effectively, thus saving ORM’s reputation as a generator of fully normalized relational schemas. But of two ways mentioned, the more satisfactory one involves, essentially, ascribing a certain semantics to the idea of “role-playing” in ORM. We show how it would address these issues, and why it is the better approach.